“FIDZ-ABCT” MODEL TO IMPROVE CROSS INFECTION PREVENTION ON TOOTH EXTRACTION - Fidzah Nurfajrina Murad; Diyah Fatmasari; Tri Wiyatini (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: The profession of dental and oral therapist (TGM) has a high risk of disease transmission, so it is important to prevent cross-infection in dental extraction services because they come into direct contact with the patient's body fluids. The description of TGM behavior in Maros Regency in preventing cross infection is not optimal, 50% do not carry out SOPs properly, 63% do not maintain hand hygiene, 50% do not change handscoons and sterile masks every time they change patients. Efforts are needed to increase cross-infection prevention behavior with the "Fidz-ABCT" Model as an educational model based on learning by doing training with the aim of improving TGM behavior in preventing cross-infection during tooth extraction procedures in community health centers. Objective: To prove the effectiveness of implementing the "Fidz-ABCT" educational model in improving TGM behavior towards preventing cross infection during tooth extraction procedures at community health centers. Method: Research and Development research design Quasy Experiment Pre-test and Post-test Control Group Design. The research subjects were TGM, 14 intervention people were given the "Fidz-ABCT" model, 14 control people were given counseling on the PPI guidebook at the community health center. Data collection techniques were interviews, questionnaires, and measuring the number of bacteria on dental extraction tools. Data were processed using the Wilcoxon test and Mann-Whitney test. Results: The "Fidz-ABCT" model is suitable for use in improving TGM behavior in preventing cross-infection during tooth extraction procedures at health centers, expert validation results are 85% and p-value 0.013 (p<0.05). The results of the delta test stated that its implementation was effective in increasing knowledge of intervention (?=5.57) control (?=1.50), attitude of intervention (?=14.21) control (?=5.07), intervention action (?=7, 42) control (?=1.64), effective in reducing the number of bacteria on dental extraction tools (p-value 0.012). Conclusion: The application of the "Fidz-ABCT" educational model is feasible and effective in increasing TGM behavior in preventing cross-infection during tooth extraction procedures at community health centers.